Journalism and conflict in Indonesia : from reporting violence to promoting peace - Sharp, Steve (New York : Routledge, 2013)
"This book examines, through the case study of Indonesia over recent decades, how the reporting of violence can drive the escalation of violence, and how journalists can alter their reporting practices in order to have the opposite effect and promote peace"--Supplied by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Journalism -- Social aspects -- Indonesia; Violence -- Press coverage -- Indonesia; Social conflict -- Press coverage -- Indonesia; Conflict management -- Press coverage -- Indonesia; Peace-building -- Press coverage -- Indonesia; Mass media and peace -- Indonesia; Electronic books